Association between levels of IgG antibodies from vaccines and Omicron symptomatic infection among children and adolescents in China - Chen, Xinying; Hong, Junbin; Deng, Lijun; Weng, Heng; Huang, Teng; Wang, Li; Ou, Aihua; Li, Yuxia; Yu, Bo; Guo, Jianwen; Yang, Jinghua (Frontiers in Medicine, 2023)
Background: Measurements of IgG antibodies to wild-type SARS-CoV-2 antigens can assess vaccine efficacy, but the absolute risk of Omicron symptomatic infection at different IgG levels for children and adolescents remains uncertain, as well as the minimum effective antibody level. We sought to determine the relationship between the tertiles of IgG antibodies to wild-type SARS-CoV-2 antigens and children with symptomatic infection of the pandemic and duration to negative conversion in China for the first time.Methods: A retrospective study was conducted, including 168 participants under 18 years old from the No.2 People's Hospital of Lanzhou, China, diagnosed with Omicron variant BA.2.38 between July 8, 2022, and August 2, 2022. We calculated odds ratios (OR) in univariate and multivariate regression to assess the association of symptomatic infection with the tertiles of IgG, respectively. Kaplan-Meier curves and Cox proportional hazards regression were used to evaluate the relationship between IgG level and negative conversion time.The average age of the 168 children included in this study was 7.2 (4.7) years old, 133 (79.2%) were symptomatic patients, and the average negative conversion time was 12.2 (3.5) days. The participants with high IgG levels were less likely to become symptomatic, had a shorter turnaround time, and had higher values of IgM and nucleic acid CT. Compared to those with the lowest tertile of IgG, patients with the highest tertile had a 914% lower risk of developing a symptomatic infection after fully adjusting for confounders (OR = 0.096, 95% CI, 0.021-0.36, P = 0.0012). There's no robust relationship between IgG level and negative conversion time in multivariate Cox regression.The risk of developing a symptomatic infection can be predicted independently by tertiles of IgG antibodies to wild-type SARS-CoV-2 antigens. High IgG levels can inhibit viral replication, vastly reduce the risk of symptomatic infections and promote a virus-negative conversion, especially when IgG quantitative detection was ≥3.44 S/CO, a potential threshold for protection and booster strategy in the future. More data and research are needed in the future to validate the predictive models.